2005
DOI: 10.1016/j.ijheatmasstransfer.2005.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer of combusting monodisperse droplets in a linear stream

Abstract: Heat and mass transfer phenomena in fuel sprays is a key issue in the field of the design of the combustion chambers where the fuel is injected on a liquid form. The development and validation of new physical models related to heat transfer and evaporation in sprays requires reliable experimental data. This paper reports on an experimental study of the energy budget, i.e. internal flux, evaporation flux and convective heat flux for monodisperse combusting droplets in linear stream. The evaporation flux is char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…They demonstrated that the reduction in the heat and mass transfers can differ between the liquid fuels even at identical distance parameters and Reynolds numbers. They also observed significantly greater reductions than those reported by Castanet et al (2005) for combusting droplets. These differences were attributed to the fuel volatility.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…They demonstrated that the reduction in the heat and mass transfers can differ between the liquid fuels even at identical distance parameters and Reynolds numbers. They also observed significantly greater reductions than those reported by Castanet et al (2005) for combusting droplets. These differences were attributed to the fuel volatility.…”
Section: Introductionmentioning
confidence: 57%
“…Important parameters such as the distance between the droplets are modified in order to characterize their influence on the droplet evaporation. Monodisperse droplet streams have been used in previous studies of droplet evaporation (Castanet et al 2005(Castanet et al , 2011Deprédurand et al 2010;Virepinte et al 2000). These studies emphasized the role of the dimensionless spacing parameter C, defined as the ratio between the droplet spacing L and the droplet size d. For low values of C, the heating and evaporation rates are reduced in comparison with the isolated droplet whose evolution can be predicted using classical models (Abramzon and Sirignano 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This function depends on both fluorescent dye and solvent of interest. An interesting side consequence of this model concerns the case of evaporating or combusting droplets (Castanet et al 2003 andCastanet et al 2005). In these cases, the droplets diameter decreases continuously due to the evaporation of the volatile fuel.…”
Section: Discussionmentioning
confidence: 99%
“…[4]). This assumption contradicts direct measurements of the temperature distribution inside droplets [5,6]. Bertoli and na Migliaccio [7] were perhaps the first to draw attention to the fact that taking into account the temperature gradient inside droplets can considerably increase the accuracy of the CFD modelling of combustion processes in Diesel engines.…”
Section: Introductionmentioning
confidence: 99%